A Study on the Impact for Proactive Personality of College Students on Entrepreneurial Intention: An Empirical Study Based on the Theory of Planned Behavior - Xu , Han; Xingguang, Li (Journal of Roi Kaensarn Academi, 2024)
Entrepreneurial activities are an important driving force for the development of modern economic and social development, and have become an important engine for economic growth in today’s era. Among the relevant studies on college students’ entrepreneurship, entrepreneurial intention, as the best entry point for the study of entrepreneurial behavior, has become the focus of entrepreneurship research, and the theory of planned behavior is the most effective theory for studying entrepreneurial intention. At the same time, research on issues such as college students’ proactive personality and self-efficacy has gradually attracted the attention of the academic community in recent years. The results show that 1. There is a significant positive correlation between proactive personality and entrepreneurial intention in the model, and the stronger the proactive personality, the higher the entrepreneurial intention. The fitting indexes of the structural equation model (SEM) all reached the ideal value, indicating that the model fits well and all paths are significant. Among them, proactive personality positively affects self-efficacy, entrepreneurial attitude, subjective norms and perceived behavioral control, and these factors further positively affect entrepreneurial intention. 2. The mediation analysis found that perceived behavioral control, subjective norms, entrepreneurial attitude and self-efficacy play a partial mediating role between proactive personality and entrepreneurial intention. 3. The mediation analysis shows that family self-employment has a significant positive moderating effect on the relationship between proactive personality and entrepreneurial intention. College students with a family self-employment background scored significantly lower than those without a family self-employment background in goal intention, execution intention, motivation, resilience, transformativeness, self-efficacy, entrepreneurial attitude, subjective norms, perceived behavioral control, and entrepreneurial intention.